Analisis dan Perancangan Sistem Informasi Manajemen Penelitian Dan Pengabdian Kepada Masyarakat Pada (LPPM) Universitas Jambi - Saputra, Fadli Iman; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2020)
Research and Community service is an activity that includes efforts to improve the quality of human resources,among others, in terms of expanding knowledge, knowledge and skill enhancement carried out by the academicsas a manifestation of dharma bakti and a form of caring to play an active role in enhancing prosperity andempowering the wider community for the economic community weak. The purpose of this study is to improvethe function of information technology that is developing at this time, and also make it easier for agencies andother parties who need data in processing and accessing data. Where in the process of data processing researchand Community Service at the Institute of Research and Community Service of the University of Jambi, stillusing conventional methods and not maximal as in the processing of research data and community servicewhich still often occurs delays in collecting proposals and processing research data and dedication to society.The system development method used to design applications, the author uses the Prototype Method, this methodis one method that is widely used in software development. This study produced a Management InformationSystem prototype design at the Institute of Research and Community Service of the University of Jambi whichcould help the Jambi University Research and Community Service Institution in accelerating the management ofresearch data and community service in the form of research and service reports, assignments , research andservice contract letters, and a certificate of completion of research and service and others.